Electrochemically Activated Reduced Graphene Oxide Used as Solid-State Symmetric Supercapacitor: An X-ray Absorption Spectroscopic Investigation - Chang, Han-Wei; Lu, Ying-Rui; Chen, Jeng-Lung; Chen, Chi-Liang; Chen, Jin-Ming; Tsai, Yu-Chen; Chou, Wu Ching; Dong, Chung-Li (My University, 2016)
A solid-state symmetric supercapacitor is successfully fabricated by assembling the sulfuric acidpoly(vinyl alcohol) (H2SO4-PVA) gel electrolyte between the two pieces of electrochemically activated reduced graphene oxide (aRGO) electrodes. The electrochemical and electronic properties of reduced graphene oxide (RGO) and aRGO were characterized by ex situ X-ray absorption spectroscopy (XAS). The aRGO exhibits better electrochemical supercapacitive performances than RGO, owing to the conjunction of the electrochemical double-layer capacitance (EDLC) and the pseudocapacitance. The specific capacitance increases with the oxygen-containing functional groups content in the electrochemically activated aRGO than RGO, increasing the pseudocapacitive contribution. The aRGO20//aRGO20 solid-state symmetric supercapacitors (SSC) exhibit an energy density of 4.7 Wh kg(-1) at a power density of 402 W kg(-1) and 4 Wh kg(-1) at a power density of 1989 W kg(-1), which is competitive with the commercially available supercapacitors. To elucidate the atomic and electronic structures of the RGO and aRGO electrodes in the charge/discharge process, ex situ XAS at the C and O K-edge were performed. Both RGO and aRGO electrodes exhibit a reversible energy shift of the O K-edge, owing to the reversible redox pseudocapacitance close to the surface of graphene-based materials. However, the absorption edge of O K-edge for aRGO electrodes shifts more significantly than that for RGO electrodes during the charge/discharge process. The results indicate that aRGO electrodes exhibit rapid and more active redox reactions for pseudocapacitance than the RGO electrodes. The results herein suggest potential use in high-performance symmetric supercapacitors.